Experience of the cleft lip and palate clinic at the hospital general de México 2017-2023 - Azcue, Arsenio F. Araujo; González, Ricardo R. Peña; Salazar-Del-Pino, Claudia P.; U., Nadia B. Quiroz; Z., Silverio Tovar (International Journal of Research in Medical Sciences, 2023)
Background: The care of cleft lip and palate patients at the general hospital of Mexico has nearly 70 years of experience. Methods: An observational study of a 7-year cohort of resolved cases of cleft lip and palate by the plastic and reconstructive surgery service of the general hospital of Mexico (2017-2023) was conducted. Results: The 121 patients were recorded, with 47 palatoplasties, 44 primary cheiloplasties, 24 secondary cheiloplasties, and 11 veloplasties performed. All patients are evaluated by a multidisciplinary team composed of plastic surgery, dentistry, clinical nutrition, speech therapy, audiology, genetics, and psychology to determine a comprehensive treatment plan. Conclusions: The data reported by the cohort in this work aligns with international reports. The frequency of cases decreased due to the COVID-19 pandemic, but has increased in recent years.